[LB.01.13] THE USE OF CARDIOVASCULAR PREVENTIVE DRUGS IN SUBJECTS AFTER MYOCARDIAL INFARCTION. A POPULATION BASED STUDY. (September 2017) - Redon, J.; Sanchis, J.; Uso, R.; Trillo, J.L.; Fernandez, A.; Morales, F.; Orozco, D.; Gil, V.
Abstract : Objective: Drug treatment for secondary prevention of cardiovascular disease is an established strategy recommended by guidelines. However, a wide gap exists between what the guidelines say and the real life in terms of number of drugs. The objective of the SATURNO study was to assess what is the gap in subjects after myocardial infarction (MI) based on Electronic Health Records (EHR). Design and method: Patients with a diagnosis of MI before to January 1st, 2012 were selected from the EHR of the Valencia Community which contain all drug prescriptions. In the present study, three groups of therapy usually recommended for secondary prevention or for control of main cardiovascular risk factors were selected: aspirin, SRA blockers (ACEi, ARB), beta-blcokers and statins. Assessment of treatment was performed after 6.1+3.5 yr of the event. Results: A total of 72784 patients (76% men, mean age 63 yr) were included. Among them, 14484 (20%) were not taking drug of the three groups, 3023 (4%) one, 9100 (13%) two and 45774 (63%) three. Concerning the kind of drugs, aspirin was present in 70%, followed by 70% SRA blockers and 68% statins. The beta-blockers were included in the treatment of 42824 (59_%) subjects. The beta-blockers when administrated in more than 80% of the cases were combined with statins, aspirin or SRA blockers. Conclusions: The proportion of patients taking cardiovascular preventive drugs after a MI is low in the general population. Several factors can contribute to it, but physician inertia and low patient compliance requires action in order to improve the secondary prevention.